Hofmannsthal and his Publishers. - Honold, Alexander (Germanic Review)
As this essay shows, Hugo von Hofmannsthal's writing was closely intertwined with the literary institutions and the public sphere of his time. His artistic development can therefore be characterized by important paradigmatic changes that lead from the influence of Stefan George and the Viennese fin-de-siècle poets to the spectacular intermedial collaborations with Max Reinhardt and Richard Strauss that successfully brought Hofmannsthal's imaginings to international stages. While negotiating the edition of his collected works with his Berlin publisher Samuel Fischer in the early 1920s, Hofmannsthal realized that his oeuvre likely appeared far too inconsistent to the public and was even in danger of dissipating, as his literary signature had changed in style and form various times, regarding the specific conditions for which his texts were made. Thus, gaining a convincing publishing policy for Hofmannsthal signified nothing less than establishing a coherent appearance for his life-work as a whole.